Synthesis and Characterization of Novel Aromatic Polyamides Based on New Aromatic Poly(phosphazene-diamine) Monomer - Zhao, Zhengping; Guo, Qiang; Zhang, Sigang; Sun, Jinliang; Nie, Zhijun (Asian Journal of Chemistry, 2011)
A new amino-terminated oligomer containing ether groups, 2,2-bis(4-amino-4,4-oxybisbenzene)- tetraphenoxyoligocyclotriphosphazene (AOPP) was synthesized. 2,2-Bis(4-amino-4,4- oxybisbenzen)tetraphenoxyoligocyclotriphosphazene was characterized using FT-IR, 1H NMR and thermal analyses. New aromatic phosphazene polyamides were prepared by polycondensation reaction of synthesized aromatic diamine with terephthaloyl dichloride. Polyamide properties were investigated by DSC, TGA, GPC (gel permeation chromatographic analysis) and wideangle X-ray scattering, viscosity and solubility measurements. The polyamides show excellent thermal stability, low-temperature resistance and solubility in polar aprotic solvents.